Turnover of exogenous artificial surfactant. Issue 4 (April 1992) - Ashton, M R; Postle, A D; Hall, M A; Austin, N C; Smith, D E; Normand, I C
Abstract : The turnover of the artificial surfactant Exosurf after its administration to infants with respiratory distress syndrome was studied. High performance liquid chromatography was used to compare the phosphatidylcholine (PC) composition of serial endotracheal tube secretions from three groups of infants. There were 22 infants who received two doses of Exosurf in 24 hours (group 1), 10 infants who received four doses in 36 hours (group 2), and 41 control infants who did not receive Exosurf. Two parameters were studied: (i) dipalmitoylphosphatidylcholine (DPPC), which is present in both Exosurf and endogenous surfactant, expressed as a percentage of total PC (% DPPC) and (ii) the ratio of DPPC to the entirely endogenous palmitoyloleoylphosphatidylcholine (DPPC:POPC ratio). The administration of Exosurf produced changes in endotracheal tube aspirate PC composition that were detectable for over one week. Four doses of Exosurf in 36 hours prolonged the persistence of these changes compared with two doses in 24 hours, but the numbers of infants were small, and should not be over-interpreted. We conclude that after giving two doses of Exosurf, further doses might best be delayed until after two days, and that further clinical evaluation of dosage regimens is required.